Works execution organization at reconstruction and renovation of buildings after the fire with usage of slabs lifting method - E. Zyma, O; V. Dyachenko, E; I. Pahomov, R; M. Zhyhylii, S (International Journal of Engineering and Technology, 2018)
Works execution organization at reconstruction and renovation of residential and public buildings after the fire for embedded systems with usage of slabs lifting method at restrained urban conditions were considered. The paper suggests usage features of the slabs lifting method at building reconstruction conditions after the fire. The technology of reconstruction with the usage of slabs lifting method allows to practically refuse the use of lifting cranes and to reduce significantly (up to 50%) the required building area compared with the lifting crane construction methods of embedded structures. It allows to perform the reconstruction without restriction of traffic on adjoining streets and to perform construction in restrained urban conditions.Â